2019
DOI: 10.1111/dom.13882
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of gemigliptin and dapagliflozin on glycaemic variability in type 2 diabetes: A randomized, open‐label, active‐controlled, 12‐week study (STABLE II study)

Abstract: Aims The aim of this study was to compare the effect of gemigliptin, a dipeptidyl peptidase‐4 inhibitor, and dapagliflozin, a sodium glucose co‐transporter‐2 inhibitor, on glycaemic variability in type 2 diabetes patients. Materials and methods In this randomized, blinded end point, multicentre clinical trial, we enrolled 71 patients with type 2 diabetes who were inadequately controlled with metformin alone or were drug naïve. The participants were randomized to receive gemigliptin 50 mg (n = 35) or dapagliflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 31 publications
0
32
1
Order By: Relevance
“…Also, our data from the linear mixed-effects model showed a rapid BG drop during hemodialysis and a tendency for hypoglycemia in the subsequent nighttime period in maintenance hemodialysis patients with type 2 diabetes. Although DPP-4 inhibitors have been shown to improve BG variability in patients with type 2 diabetes in many randomized controlled trials (RCTs) [41][42][43][44][45][46][47][48][49] (see the table in the Electronic supplementary material), few studies have reported the same effect in maintenance hemodialysis patients [50]. Our study illustrates the usefulness of DPP-4 inhibitors in these patients.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Also, our data from the linear mixed-effects model showed a rapid BG drop during hemodialysis and a tendency for hypoglycemia in the subsequent nighttime period in maintenance hemodialysis patients with type 2 diabetes. Although DPP-4 inhibitors have been shown to improve BG variability in patients with type 2 diabetes in many randomized controlled trials (RCTs) [41][42][43][44][45][46][47][48][49] (see the table in the Electronic supplementary material), few studies have reported the same effect in maintenance hemodialysis patients [50]. Our study illustrates the usefulness of DPP-4 inhibitors in these patients.…”
Section: Discussionmentioning
confidence: 54%
“…The ability of DPP-4 inhibitors to suppress BG variability in patients with type 2 diabetes has been shown in studies using CGM [51, 52]. Furthermore, several RCTs using CGM found that BG variability is suppressed more effectively by DPP-4 inhibitors than by other agents such as sulfonylureas [41,42] and sodium glucose cotransporter 2 inhibitors [43][44][45] [41,49], or had used metformin only [41][42][43]46]. There have also been some reports on the usefulness of DPP-4 inhibitors in patients on hemodialysis [50], but none has shown obvious suppression of BG variability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diabetes Metab J 2020;44:828-839 https://e-dmj.org vidual short-term glycemic status for determining the efficacy and safety of new drugs and devices, comparing drugs in improving glycemic status, or evaluating the correlation with chronic diabetic complications [30,33,[49][50][51]. When using real-time CGM, the patient can modify behavior such as diet, exercise, medication, or insulin dose in response to real-time changing data, which can affect the outcome of the study [52,53].…”
Section: Differences Between Professional and Personal Cgmmentioning
confidence: 99%